1978
DOI: 10.1002/polc.5070630120
|View full text |Cite
|
Sign up to set email alerts
|

Crystal nucleation and the crystalmelt interfacial tension in linear hydrocarbons

Abstract: Recent results on the homogeneous nucleation of crystals in n‐alkane (CnH2n+2) melts are used in conjunction with simple nucleation theory to calculate scaled crystal‐melt interfacial tensions, α (n), per CH2 group. α(n) falls off smoothly and, at first, sharply with n increasing to 12–15, where it levels and remains roughly constant at ca. 0.15 to n = 32, at least. We show that these results are accounted for satisfactorily by the Spaepen‐Meyer negentropic model for the crystal‐melt tension, if it is assumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…The result is a weak value of the scaled interfacial tension. It is the situation considered in the negentropic model of Spaepen 30,34 (see Fig. 12).…”
Section: Discussionmentioning
confidence: 99%
“…The result is a weak value of the scaled interfacial tension. It is the situation considered in the negentropic model of Spaepen 30,34 (see Fig. 12).…”
Section: Discussionmentioning
confidence: 99%
“…Liquid atoms at the crystal–liquid interface cannot adopt as many configurations as in the bulk because of the special boundary conditions of the crystal plane. This concept was introduced into the systems of n ‐alkanes as the negentropic model by Turnbull and Spaepen 38. They found that scaled crystal‐melt interfacial tensions fall off asymptotically to a constant value with increasing chain length; they explained this by the segmental nature of n ‐alkane chains.…”
Section: Discussionmentioning
confidence: 99%
“…The CO 2 molar density at the experimentally observed kink point for octacosane is 5910 mol/m 3 ; for C28 with ethane it is 6620 mol/m 3 , and for C28 with ethylene it is 4030 mol/m 3 . These values are comparable to the molar density of a Kuhn monomer unit of a pure octacosane melt, 8500 mol/m 3 [30]. Hence, we adopt the Kuhn monomer unit as the molar volume unit, u, for describing the behavior of polymers.…”
Section: Slope Change At Higher Pressurementioning
confidence: 98%